2021
DOI: 10.37193/cjm.2022.01.17
|View full text |Cite
|
Sign up to set email alerts
|

Center problem for cubic differential systems with the line at infinity of multiplicity four

Abstract: In this paper the center problem for cubic differential systems with the line at infinity of multiplicity four is solved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…According to [11], the line at infinity in complex variables 𝐴, 𝐵, ..., 𝑅, 𝑆 has the multiplicity at least four for cubic system {(1), (2)} if and only if the coefficients of {(1),(2)} verify one of the following two sets of conditions:…”
Section: Cubic Systems With the Line At Infinity Of Multiplicity Fourmentioning
confidence: 99%
See 3 more Smart Citations
“…According to [11], the line at infinity in complex variables 𝐴, 𝐵, ..., 𝑅, 𝑆 has the multiplicity at least four for cubic system {(1), (2)} if and only if the coefficients of {(1),(2)} verify one of the following two sets of conditions:…”
Section: Cubic Systems With the Line At Infinity Of Multiplicity Fourmentioning
confidence: 99%
“…In [11], using the variables 𝐴, 𝐵, ..., 𝑅, 𝑆, it was shown that the line at infinity in (1) has multiplicity two if and only if one of the following three sets of conditions holds:…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The problem of the center was solved for some families of cubic differential systems having invariant algebraic curves (invariant straight lines, invariant conics, invariant cubics) in [5], [7], [9], [10], [12], [13], [16], [19], [20], [21]. Center conditions were determined for some cubic systems having integrating factors in [8], [11], [14], for some reversible cubic systems in [2] and for a few families of the complex cubic system in [15].…”
Section: Cozma Dmentioning
confidence: 99%